Editor’s Highlight: CCR2 Regulates Inflammatory Cell Accumulation in the Lung and Tissue Injury following Ozone Exposure - Francis, Mary (Toxicol Sci, 2017)
Ozone-induced lung injury is associated with an accumulation of activated macrophages in the lung. Chemokine receptor CCR2 mediates the migration of inflammatory monocytes/macrophages to sites of tissue injury. It is also required for monocyte egress from the bone marrow. In the present studies, we analyzed the role of CCR2 in inflammatory cell trafficking to the lung in response to ozone. Treatment of mice with ozone (0.8 ppm, 3 h) resulted in increases in proinflammatory CCR2(+) macrophages in the lung at 24 h, as well as proinflammatory CD11b (+) Ly6C(Hi) and iNOS(+) macrophages at 24 and 48 h. Mannose receptor(+) anti-inflammatory macrophages were also observed in the lung 24 and 48 h post-ozone. Loss of CCR2 was associated with reduced numbers of proinflammatory macrophages in the lung and decreased expression of the proinflammatory cytokines, IL-1β and TNFα. Decreases in anti-inflammatory CD11b (+) Ly6C(Lo) macrophages were also observed in lungs of CCR2(−/−) mice treated with ozone, whereas mannose receptor(+ )macrophage accumulation was delayed; conversely, CX3CL1 and CX3CR1 were upregulated. Changes in lung macrophage subpopulations and inflammatory gene expression in CCR2(−/−) mice were correlated with reduced ozone toxicity and oxidative stress, as measured by decreases in bronchoalveolar lavage protein content and reduced lung expression of heme-oxygenase-1, 4-hydroxynonenal and cytochrome b5. These data demonstrate that CCR2 plays a role in both pro- and anti-inflammatory macrophage accumulation in the lung following ozone exposure. The fact that ozone-induced lung injury and oxidative stress are reduced in CCR2(−/−) mice suggests more prominent effects on proinflammatory macrophages.